2014
DOI: 10.5455/2320-1770.ijrcog20140342
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of perineal tear during childbirth by assessment of striae gravidarum score

Abstract: Background:The objective of this study was to explore the association between striae gravidarum and the risk for perineal tear during childbirth. Methods: Three hundred patients delivered normally were included in this study. Striae gravidarum score was assessed using the Atwal numerical scoring system. The association was examined between striae and perineal tear as the outcome measure, defined by tears or laceration, and the total striae scores (TSS) was obtained. Results: Mean age was 25.41 years ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 13 publications
1
15
0
2
Order By: Relevance
“…As expected and previously showed by others [1,3], our study found a statistically significant association between abdominal adhesions and the number of previous cesarean sections. Kapadia et al reported on the effect of connective tissue collagen on skin elasticity [18]. They found that perineal lacerations were more common during vaginal delivery in patients with striae gravidarum secondary to defective collagen synthesis.…”
Section: Association Between Abdominal Striae and Adhesions Accordingmentioning
confidence: 99%
“…As expected and previously showed by others [1,3], our study found a statistically significant association between abdominal adhesions and the number of previous cesarean sections. Kapadia et al reported on the effect of connective tissue collagen on skin elasticity [18]. They found that perineal lacerations were more common during vaginal delivery in patients with striae gravidarum secondary to defective collagen synthesis.…”
Section: Association Between Abdominal Striae and Adhesions Accordingmentioning
confidence: 99%
“…Therefore, this study found that episiotomy has some protective effect against PT. Kapadia et al 13 also showed similar result. To investigate the role of SG score in predicting the risk for PT, logistic regression analysis was done considering TSS, weight gain during pregnancy and birth weight of newborns among the 126 women in whom episiotomy was not performed.…”
Section: Discussionmentioning
confidence: 53%
“…10 Striae gravidarum merupakan penanda elastisitas kulit dan otot, sehingga sangat penting melakukan investigasi striae gravidarum pada wanita hamil yang akan menjalani persalinan karena berhubungan dengan bagaimana penolong melakukan tindakan menjaga keutuhan perineum atau meminimalkan laserasi perineum pada persalinan. 11 Hipotesis penelitian ini adalah wanita dengan striae gravidarum sedang-berat cenderung mengalami laserasi perineum dibandingkan dengan wanita tanpa striae gravidarum-striae gravidarum ringan.…”
Section: Pendahuluanunclassified
“…15 Kolagen, elastin, dan serat fibrilin menurun pada wanita dengan striae gravidarum dibandingkan dengan wanita dengan kulit yang utuh tanpa striae gravidraum. 11 Primigravida lebih banyak memiliki skor striae gravidarum yang lebih tinggi dibandingkan dengan multigravida. 16 Striae gravidarum sendiri tidak dapat ditunjuk sebagai penyebab langsung trauma perineum, tetapi striae gravidarum merupakan atribut penurunan elastisitas kulit yang diidentifikasi memiliki tendensi terhadap trauma perineum.…”
Section: Gambar 1 Rancangan Penelitianunclassified